USER ACCEPTANCE OF SMART HOUSEKEEPING: A STUDY OF TAM MODEL PROTOTYPE IN HOTEL INDUSTRY - Hamid, Rasidah; Mohd Hashim, Nor Hanisah; Abdul Razak, Intan Rahayu; Tuan Ismail, Tuan Ahmad; Ramli, Noorazlin; Mohi, Zurinawati; Wan Nawawi, Wan Nazriah; Baba, Noradzhar (International Journal of Supply Chain Management, 2020)
Â Abstractâ??An empirical assessment of the theoretical framework for this study included a survey of 120 employees that working in 4 hotels around Klang Valley that have an experience using smart housekeeping trolley. The resulting data were analyzed using the PLS-SEM methodology by using the SmartPLS 3.0 software. The findings suggested that Perceived Usefulness, Perceived Ease of Use, and Perceived Innovativeness give a positive significant impact towards Attitude. Besides that, Attitude, Perceived Usefulness, and Perceived Ease of Use simultaneously significantly affect Intentions. In addition, Attitude gives a partial mediating effect toward the relationship of Perceived Usefulness and Perceived Ease of Use toward Intentions, but give a full mediating effect toward the relationship of Perceived Innovativeness and Intentions.Keywordsâ??PLS-SEM, Mediating Analysis